Effect of Fly Ash Variation and Heating Temperature on Physical Properties, Chemical Composition, Phase Structure, and Morphology in Making Red Brick - Rajiman Rajiman; Muhammad Amin; Sudibyo Sudibyo; Suprihatin Suprihatin; Fahda Rufaidah (Universitas Diponegoro, 2022)
Red brick is a building material that can be used as a construction material. Red bricks are made of pure clay or mixed materials. This study aimed to determine the effect of fly ash and heating temperature variations on physical properties (compressive strength, density, porosity, and absorption), chemical composition, phase structure, and morphology in brick making. The addition of fly ash by 10%, 20%, 30%, 40%, and 50% of the composition of the material is 750 grams. The red bricks were printed with a size of 5 x 5 x 5 cm3, heated at 700°C and 800°C for 2 hours, and soaked for 24 hours. Physical tests include compressive strength test, density test, porosity test, and absorption test, as well as red brick characterization, namely XRF, XRD, and SEM-EDS. Red brick with sample A10 at a temperature of 700°C has the highest compressive strength value of 3.68 Mpa, while red brick with sample A10 at a temperature of 800 °C has the highest compressive strength value of 4.17 Mpa. Characterization shows that the phases formed in red brick are quartz (SiO2), hematite (Fe2O3), and anorthite (Al2O3).